Designing Interior Architecture: Concept, Typology, Material, Construction - Leydecker, Sylvia (Birkhäuser, 2013)
Designing interior spaces is a task that is equally relevant as architecture, landscape architecture, and urban design for those working professionally in the built environment. In this comprehensive work, an international and interdisciplinary team of authors presents the essential aspects of the various fields of contemporary interior architecture and design. The project examples are illustrated with brilliant photographs and plans. They have been selected according to consistent criteria for all chapters of the book and represent the essential building types, including exhibition stand design, as well as a broad range of today's design approaches. The authors place the collaboration between the various design disciplines at the center of focus. The appendix contains information for further research. All in all, Designing Interior Architecture is a fundamental reference work for all those professionally engaged with the design.